The big green help. - Tan, Regina Chunrong. (2010)
The Big Green Help (TBGH) is a pro-social initiative which was started by Nickelodeon in 2008. The main objective of TBGH is to empower children with platforms to play an active role in making the Earth a greener planet. This paper presents the collaboration by a team of four final-year students from Nanyang Technological University’s Wee Kim Wee School of Communication and Information with Nickelodeon (Singapore). In line with Nickelodeon’s objective of empowering children to save the Earth, this campaign was developed to cultivate a group of young opinion leaders into Green Ambassadors to become the main campaign communicators, spreading the green messages to their peers. Guided by the Two-Step Flow hypothesis, Social Learning Theory and Theory of Involvement, the campaign was programmed to create platforms for Green Ambassadors to become opinion leaders and influence their peers in their awareness of environmental issues, attitudes towards caring for the environment and adoption of green behaviours. The campaign results showed an improvement in awareness of TBGH with seven in ten children indicating they knew about the Green Ambassadors and the messages they communicated. More than half of the children also indicated that they have learnt certain green behaviours from their Green Ambassadors. Nickelodeon’s TBGH campaign 2010 achieved its objectives of increasing awareness of the campaign and its key messages within the participating schools.